2019
DOI: 10.1038/s41586-019-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

A magnetar-powered X-ray transient as the aftermath of a binary neutron-star merger

Abstract: Neutron star-neutron star mergers are known to be associated with short gammaray bursts 1-4 . If the neutron star equation of state is sufficiently stiff, at least some of such mergers will leave behind a supramassive or even a stable neutron star that spins rapidly with a strong magnetic field (i.e., a magnetar) 5-8 . Such a magnetar signature may have been observed as the X-ray plateau following a good fraction (up to 50%) of short gamma-ray bursts 9, 10 , and it has been expected that one may observe short … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
181
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(217 citation statements)
references
References 56 publications
36
181
0
Order By: Relevance
“…Additionally, during the field amplification, the spin-down torque N dip responds to the magnetic dipole radiation luminosity which follows the evolution of the angular velocity of the shell, as displayed in Figure 2. This Poynting flux could generate a high energy (X-ray/γ-ray) transient lasting hundreds to thousands of seconds via magnetic dissipation with brightness up to L dip,peak ∼ 10 46 erg s −1 , which is likely similar to an X-ray transient source named CDF-S XT2 discovered by Xue et al (2019). Besides the differential rotation, Duncan & Thompson (1992) and Thompson & Duncan (1993) suggested that a key parameter for the success of α − ω dynamo is the Rossby number R O relevant to convection (the ratio of the rotation period to the convective overturn time).…”
Section: α − ω Dynamomentioning
confidence: 87%
“…Additionally, during the field amplification, the spin-down torque N dip responds to the magnetic dipole radiation luminosity which follows the evolution of the angular velocity of the shell, as displayed in Figure 2. This Poynting flux could generate a high energy (X-ray/γ-ray) transient lasting hundreds to thousands of seconds via magnetic dissipation with brightness up to L dip,peak ∼ 10 46 erg s −1 , which is likely similar to an X-ray transient source named CDF-S XT2 discovered by Xue et al (2019). Besides the differential rotation, Duncan & Thompson (1992) and Thompson & Duncan (1993) suggested that a key parameter for the success of α − ω dynamo is the Rossby number R O relevant to convection (the ratio of the rotation period to the convective overturn time).…”
Section: α − ω Dynamomentioning
confidence: 87%
“…Because of the rapid rotation, we predict that neutron stars formed in mergers have largescale magnetic fields of magnetar strength generated by a strong field convective dynamo. This will be tested with dedicated numerical simulations and future multimessenger observations (33).…”
Section: Discussionmentioning
confidence: 99%
“…The post-merger remnant may be a rapidly rotating NS with a high magnetic field (a magnetar), visible in X-ray and gamma rays (e.g. Xue et al 2019). In addition, DNS post merger remnants may also be a source of Fast Radio Bursts (FRBs, e.g.…”
Section: Post-merger Remnantmentioning
confidence: 99%